2019
DOI: 10.1051/matecconf/201929013004
|View full text |Cite
|
Sign up to set email alerts
|

Education for sustainable development

Abstract: Education for sustainable development in an intense subject and dissemination of good practices are of tremendous need for actors of academia and for those of vocational education, too. Managers and employees must extend their current skills related to sustainability and become leaders in the field. The article presents the last years’ experience on the development of a skills development schema on leadership in sustainability and teaching and educating sustainability. These two training skills and the related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition to the aforementioned report, it is worth mentioning the Club of Rome's 1972 publication "The Limits to Growth", which attempted to determine human impact on the environment (Meadows et al, 1972;Lemkowska, 2020) The very definition of sustainable development incorporates three aspects: the environment, economy and society. According to the report, sustainable development entails such manner and form of development which allows the needs of the present generation to be met without limiting the future generations' ability to meet their needs (Turner, 1988;Draghici, 2019). As Nowak M. (Nowak, 2017) notes in his study, education entails one of the conditions underlying and enabling sustainable development.…”
Section: Literature Review 21 Sustainable Educationmentioning
confidence: 99%
“…In addition to the aforementioned report, it is worth mentioning the Club of Rome's 1972 publication "The Limits to Growth", which attempted to determine human impact on the environment (Meadows et al, 1972;Lemkowska, 2020) The very definition of sustainable development incorporates three aspects: the environment, economy and society. According to the report, sustainable development entails such manner and form of development which allows the needs of the present generation to be met without limiting the future generations' ability to meet their needs (Turner, 1988;Draghici, 2019). As Nowak M. (Nowak, 2017) notes in his study, education entails one of the conditions underlying and enabling sustainable development.…”
Section: Literature Review 21 Sustainable Educationmentioning
confidence: 99%
“…So, the present study implements proper policies that should be made to increase households' awareness of higher education. Draghici (2019) examined the impact of vocational institutions' knowledge and skills in Romina. The study showed that many professional officers extend their skills and knowledge through training programs offered by vocational institutions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Through higher education, in poor countries, farmers adopted different production techniques that will increase the average income of every farmer will increase poor living standards because, in backward countries, most farmers are attached to the traditional method of farming that played very minor roles to increase the productivity of land farmer so higher education is a good way to increase per acre productivity of land farmer (Draghici, 2019;Komives et al, 2019;Lacharite, 2016) An increase in higher education and enrolment rate in poor areas will solve farmer, and agricultural problems in a good way. Modern agricultural methods with less use of physical effort and more used of machines will increase the knowledge base technological skills and development sustainability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, education for sustainable development (ESD) aims to develop competences that empower learners with knowledge, skills, values, and attitudes. ESD seeks to encourage reflection on our own actions and taking informed decisions for environmental integrity, economic viability and a just society by empowering people of all genders, for present and future generations, while respecting cultural diversity (Bagoly-Simó et al, 2018;Draghici, 2019;UNESCO, 2012UNESCO, , 2017UNESCO, , 2020. There is a global call to take action for a common future (UNESCO, 2020), to see beyond the challenges and start thinking of solutions to environmental problems.…”
Section: Introductionmentioning
confidence: 99%